plus or minus 6
x2 - 2x = x(x - 2)
x^2 - y^2 - 4 is in its simplest form.
First, you remove every x that you can from the equation. Next, you reach the simplest form of the equation, which is (7x-2)(x-2). Which is the lowest factorable form.
(5x + 2)(x - 5)
you cant really simpliffy that expression you need an equation so just write 'cannot simplify' or 'already in simplest form'
5 over 6 minus 2 in simplest form equals -1 1/6
It is: 1 and 1/6 minus 2/3 = 1/2 in its simplest form
32 + 63 = 9 + 216 = 225
It is: 7/8 minus 1/8 = 6/8 => 3/4 in its simplest form